Imbalance of the oxytocin-vasopressin system contributes to the neuropsychiatric phenotype in the BACHD mouse model of Huntington disease - Cheong, Rachel Y.; Tonetto, Simone; von Hörsten, Stephan; Petersén, Åsa (Psychoneuroendocrinology, 2020)
Neuropsychiatric disturbances with altered social cognition, depression and anxiety are among the most debilitating early features in the fatal neurodegenerative disorder Huntington disease (HD) which is caused by an expanded CAG repeat in the huntingtin gene. The underlying neurobiological mechanisms are not known. Neuropathological analyses of postmortem human HD hypothalamic tissue have demonstrated loss of the neuropeptides oxytocin and vasopressin. The dynamic interplay between these neuropeptides is crucial for modulating emotional and social behavior but its role in HD is unclear. In the present study, we have investigated the effect of expressing the mutant huntingtin gene on the development of behavioral changes using the transgenic BACHD mouse model at different ages. We show for the first time that BACHD mice exhibit deficits in social behavior with parallel aberrations in the balance of the oxytocin-vasopressin system. Importantly, our data also show that restoration of the interplay within the system with an acute dose of intranasal oxytocin immediately prior to behavioral testing can rescue the depressive-like phenotype but not anxiety-like behavior in this transgenic model. These findings demonstrate that imbalances in the oxytocin-vasopressin interplay contribute to the neuropsychiatric component of HD and suggest that interventions aimed at restoring the blunted levels of oxytocin may confer therapeutic benefits for this disease.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Huntington's disease; Hypothalamus; Neuropsychiatric behavior; Oxytocin; Vasopressin